The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/app.41760
|View full text |Cite
|
Sign up to set email alerts
|

Polymer electrolyte membranes prepared by EB‐crosslinking of sulfonated poly(ether ether ketone) with 1,4‐butanediol

Abstract: Crosslinked sulfonated poly(ether ether ketone) (SPEEK) membranes were prepared through the electron beam (EB)‐irradiation crosslinking of SPEEK/1,4‐butanediol under various irradiation conditions and used as a proton exchange membrane (PEM) for fuel cell applications. The crosslinked membranes were characterized by gel fraction, a universal testing machine (UTM), dynamic mechanical analysis (DMA), and small‐angle X‐ray scattering (SAXS). The gel fraction of the crosslinked membranes was used to estimate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…It was reported that the crosslinking could mitigate excess swelling of IEC membranes . The crosslinking could be generally made by acid–base (electrostatic) interactions or covalent bonds . The ionically crosslinked membranes are not very stable particularly at high temperature and humidity due to the relatively weak electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the crosslinking could mitigate excess swelling of IEC membranes . The crosslinking could be generally made by acid–base (electrostatic) interactions or covalent bonds . The ionically crosslinked membranes are not very stable particularly at high temperature and humidity due to the relatively weak electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Gel fraction was measured to evaluate the cross-linking degree of the membranes. The prepared membranes were immersed in ethanol at room temperature for 12 h and then dried under vacuum conditions at 60 °C for 24 h. The gel fraction was calculated according to the following equation: where m 0 (g) and m i (g) are the weights of dry membranes before and after ethanol treatment, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…While scattering experiments are largely helpful in inferring the static structure of these polymer membranes, computer simulation is another useful tool that can provide insight into the structure as well as suggest ways to tailor them. Currently, there are a number of experiments on sPEEK in pristine, branched, composite, crosslinked, and functionalized forms, aiming for high performance in terms of microphase separation, proton conductivity, and thermal and mechanical stability. However, the simulation studies on sPEEK mostly focus on linear chain systems and have relied on molecular dynamics (MD) or field theoretic models .…”
Section: Introductionmentioning
confidence: 99%